Indigenous evangelists and questions of authority in the British Empire, 1750-1940 - Brock, Peggy, 1948- (Studies in Christian Mission, 2015)
This is the first full-length historical study of indigenous evangelists across a range of societies, geographical regions and colonial regimes and the first to focus on the complex issues of authority surrounding the evangelists. It answers a need frequently voiced in recent studies of Christian missions. Most scholars now acknowledge that the remarkable expansion of Christianity in Africa, Asia and the Pacific in the nineteenth and twentieth centuries owed far more to the efforts of indigenous preachers than to the foreign missionaries who loom so large in publications. This book addresses that concern making an excellent introduction to the role of indigenous evangelists in the spread of Christianity, and the many countervailing pressures with which these individuals had to contend. It also includes in the introductory discussions useful statements of the current state of scholarship and theoretical debates in this field.